Usability testing of the Libro System - Luna edition - Melorin, Pamela P. (2010)
The study is primarily an evaluation of the design of the Libro System-Luna edition by means of a usability test. Usability test is the technique used to evaluate the system by testing it to the actual and potential users. Particularly, it aimed to know how well the Libro System - Luna edition performs in terms of task time, success rate, error rate, memorability rate and satisfaction rate. Also, it intended to gather feedback from the actual and potential users regarding the usability of Libro System - Luna edition after experiencing the usability test.